Water-soluble arene ruthenium complexes containing pyridinethiolato ligands: Synthesis, molecular structure, redox properties and anticancer activity of the cations [(η6-arene)Ru(p-SC5H4NH)3]2+ - Gras, Michaël; Therrien, Bruno; Süss-Fink, Georg; Štěpnička, Petr; Renfrew, Anna K.; Dyson, Paul J. (My University, 2008)
The cationic complexes [(η6-arene)Ru(SC5H4NH)3]2+, arene being C6H6 (1), MeC6H5 (2), p-iPrC6H4Me (3) or C6Me6 (4), have been synthesised from the reaction of 4-pyridinethiol with the corresponding precursor (η6-arene)2Ru2 (μ2-Cl)2Cl2 and isolated as the chloride salts. The single-crystal X-ray structure of [4](PF6)2 reveals three 4-pyridinethiol moieties coordinated to the ruthenium centre through the sulphur atom, with the hydrogen atom transferred from the sulphur to the nitrogen atom. The electrochemical study of 1–4 shows a clear correlation between the Ru(II)/Ru(III) redox potentials and the number of alkyl substituents at the arene ligand (E°′ (RuII/III): 1 > 2 > 3 > 4), whereas the cytotoxicity towards A2780 ovarian cancer cells follows the series 4 > 1 > 3 > 2, the hexamethylbenzene derivative 4 being the most cytotoxic one. The corresponding reaction of the ortho-isomer, 2-pyridinethiol, with (η6-C6Me6)2Ru2 (μ2-Cl)2Cl2 does not lead to the expected 2-pyridinethiolato analogue, but yields the neutral complex (η6-C6Me6)Ru(η2-SC5H4N)(η1-SC5H4N) (5). The analogous complex (η6-C6Me6)Ru(η2-SC9H6N)-(η1-SC9H6N) (6) is obtained from the similar reaction with 2-quinolinethiol.
Keywords: Ruthenium; Anticancer agents; Electrochemistry; Bioorganometallic chemistry; Arene ligands